2013
DOI: 10.1155/2013/392746
|View full text |Cite
|
Sign up to set email alerts
|

Human Leukocyte Antigen Class II Alleles (DQB1 and DRB1) as Predictors for Response to Interferon Therapy in HCV Genotype 4

Abstract: Human leukocyte antigens class II play an important role in immune response against HCV. We investigated whether HLA class II alleles influence susceptibility to HCV infection and response to interferon therapy. HLA-DRB1 and -DQB1 loci were genotyped using PCR-SSO Luminex technology. According to our regimen, 41 (66%) of patients achieved sustained virological response to combined treatment of IFN and ribavirin. Frequencies of DQB1∗0313 allele and DRB1∗04-DRB1∗11, DQB1∗0204-DQB1∗0313, DQB1∗0309-DQB1∗0313, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 48 publications
1
7
0
Order By: Relevance
“…Our result concerning HLA DRB1*13 is in agreement with Shaker et al (2013) who reported that DRB1 * 1301, DRB1 * 1361, DRB1 * 1369, DRB1 * 13 alleles to be significantly more frequent in responders than in non responders. Concerning our results of HLA DRB1 *07, we agree with Zekri et al (2005) who showed that HLA class II allele DR* 07 was significantly encountered in HCV positive family members than negative members.…”
Section: ) -------------------------------------------------------supporting
confidence: 93%
See 3 more Smart Citations
“…Our result concerning HLA DRB1*13 is in agreement with Shaker et al (2013) who reported that DRB1 * 1301, DRB1 * 1361, DRB1 * 1369, DRB1 * 13 alleles to be significantly more frequent in responders than in non responders. Concerning our results of HLA DRB1 *07, we agree with Zekri et al (2005) who showed that HLA class II allele DR* 07 was significantly encountered in HCV positive family members than negative members.…”
Section: ) -------------------------------------------------------supporting
confidence: 93%
“…Before peg-IFN therapy, diagnosis of CHC was established on persistent (>6 months) elevation of Alanine aminotransferase (ALT) concentration 1.5 times above the upper limit of normal, positive results of antibody to HCV testing, positive HCV RNA testing in serum and histological evidence of chronic hepatitis and earlier fibrosis stages (Metavir stage ≤F2). The Metavir scoring system described as follows: For activity, A0 is no histological activity, A1 mild activity, A2 moderate activity and A3 severe activity; for fibrosis, F0 is no fibrosis, F1 portal tract expansion by fibrosis, F2 less than 50% bridging fibrosis, F3 more than 50% bridging fibrosis without cirrhosis and F4 established cirrhosis (Shaker et al, 2013). They were followed from March 2012 to March 2014 at outpatient clinics of hepatology unit, Al-Ahrar Hospital (Zagazig, Egypt) under the supervision of the National Committee for the Control of Viral Hepatitis (NCCVH).…”
Section: Study Populationmentioning
confidence: 99%
See 2 more Smart Citations
“…Eighty-four studies were closely evaluated for eligibility[1016, 18, 26101]. Fourteen studies did not have extractable treatment outcomes data[26, 29, 36, 47, 50, 58, 61, 64, 74, 86, 87, 92, 100, 101]. Six were redundant[49, 51, 57, 68, 89, 99] and four were not relevant[30, 43, 60, 94].…”
Section: Resultsmentioning
confidence: 99%